Present : Kulturlandskap - Akersvika : Keramikk - Ringebu : Akersvika - Addenda. (Lillehammer : LOOC Culture Section, 1993)
Kuniyasu, Takamasa ; Hafstrom, Jan ; Andersen, Finn Aage ; Eckhoff, Wenche K. ; Astala, Lauri ; O'Connell, Eilis ; Fujiwara, Makoto ; Wold, Knut
Kulturlandskap - Akersvika, Akersvika (natuurreservaat), Hamar, 20.08.93 - 15.08.94
boek